2023
DOI: 10.1001/jama.2022.20954
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Dementia Prevalence in Older Adults in the US

Abstract: This study assesses the association of audiometric hearing loss and hearing aid use with dementia among community-dwelling older US Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…A recent national study found an 11.46% prevalence of dementia in hearing aid device (HAD) users, with a dose-response relationship between HL severity and dementia prevalence [26]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…A recent national study found an 11.46% prevalence of dementia in hearing aid device (HAD) users, with a dose-response relationship between HL severity and dementia prevalence [26]. Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Hearing loss has been associated with a wide variety of physical and mental health risks, including social isolation, depression, lower quality of life and a significantly elevated risk of dementia [8,9,10]. On average, individuals wait 9 years from hearing aid candidacy to hearing aid adoption, while earlier adoption may mitigate some of the risks associated with hearing loss [11,12].…”
Section: Problemmentioning
confidence: 99%
“…Hearing loss has gained public health interest as an important factor affecting healthy aging. It is associated with cognitive decline, impaired physical function, poorer health resource utilization, and dementia . Importantly, evidence suggests that hearing treatment may mitigate these associations and prevent poor health outcomes, spurring federal agency actions and Congressional legislation to address hearing loss in the US .…”
Section: Introductionmentioning
confidence: 99%